2017
DOI: 10.1128/mbio.00126-17
|View full text |Cite
|
Sign up to set email alerts
|

The Vibrio cholerae VexGH RND Efflux System Maintains Cellular Homeostasis by Effluxing Vibriobactin

Abstract: Resistance-nodulation-division (RND) superfamily efflux systems have been widely studied for their role in antibiotic resistance, but their native biological functions remain poorly understood. We previously showed that loss of RND-mediated efflux in Vibrio cholerae resulted in activation of the Cpx two-component regulatory system, which mediates adaptation to stress resulting from misfolded membrane proteins. Here, we investigated the mechanism linking RND-mediated efflux to the Cpx response. We performed tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 57 publications
4
39
0
Order By: Relevance
“…In this regard, it is known that electron flow leads to the generation of damaging reactive oxygen species (48), which could theoretically result in damage to respiratory complexes or other protein assemblies and a Cpx-inducing signal. In agreement with this model, Bina and coworkers recently showed in Vibrio cholerae that the inability to efflux the siderophore vibriobactin, as well as the oxidative-stress-inducing agent paraquat, resulted in Cpx pathway induction in an oxygendependent manner (49). Additionally, Chao and Vogel (50) demonstrated that the Cpx response is activated by the protonophore carbonyl cyanide m-chlorophenylhydrazone (CCCP) in Salmonella, suggesting that disruption of the proton-pumping activity associated with these complexes could also potentially be the source of a Cpx-activating signal.…”
Section: Discussionmentioning
confidence: 71%
“…In this regard, it is known that electron flow leads to the generation of damaging reactive oxygen species (48), which could theoretically result in damage to respiratory complexes or other protein assemblies and a Cpx-inducing signal. In agreement with this model, Bina and coworkers recently showed in Vibrio cholerae that the inability to efflux the siderophore vibriobactin, as well as the oxidative-stress-inducing agent paraquat, resulted in Cpx pathway induction in an oxygendependent manner (49). Additionally, Chao and Vogel (50) demonstrated that the Cpx response is activated by the protonophore carbonyl cyanide m-chlorophenylhydrazone (CCCP) in Salmonella, suggesting that disruption of the proton-pumping activity associated with these complexes could also potentially be the source of a Cpx-activating signal.…”
Section: Discussionmentioning
confidence: 71%
“…Transport proteins that showed differential accumulation included anaerobic C4‐dicarboxylate transporter‐DcuC, which participates in the succinate flow system during anaerobic fermentation of glucose ; efflux RND‐transporter periplasmic adaptor subunit, which carries factors of resistance, nodulation and cell division ; long‐chain fatty acid transporter, which drives mobilization of long chain fatty acids, either outside or inside the cell, or between cells ; MFS transporter, which facilitates transport of ions, sugar phosphates, drugs, neurotransmitters, nucleosides, amino acids and peptides ; multidrug efflux RND‐transporter permease subunit, which is responsible for transporting cadmium, zinc and cobalt ; and multidrug transporter‐AcrB, which cooperates with a membrane fusion protein, AcrA, and a TolC outer membrane channel .…”
Section: Resultsmentioning
confidence: 99%
“…Vibriobactin, a siderophore, is produced by V. cholerae and is secreted out of the cell to bind iron and bring it back to the cytoplasm through the RND system (Griffiths et al ., ). In the absence of RND efflux, vibriobactin is unable to exit the cell and chelates iron within the cell to generate an activation signal for Cpx (Kunkle et al ., ). While the role of Cpx in iron scavenging has only been examined under virulence inducing conditions (Taylor et al ., ), it would be interesting to determine if the Cpx response is induced when Vibrio colonizes aquatic hosts and/or in seawater.…”
Section: The Cpx Responsementioning
confidence: 97%